Quantification of iodine in salt, foods; and determination of knowledge and pattern of consumption of iodine containing food materials in Sokoto State, Nigeria - Umar Imam, Aminu; Sarkingobir, Yusuf; Tukur, Ummu (Kalasin University Journal of Science Technology and Innovation, 2024)
The objectives were to assess iodine in food materials and commercial salts in Sokoto; assess consumption of iodine rich foods, and assess knowledge about iodine nutrition. Questionnaire was utilized to collect the qualitative data, and levels of iodine were determined with standard methods. The design was done in quasi experimental fashion. All study subjects passed through these stages of grouping exercise namely, pre-test group, Intact group and post-test group design. The levels of iodine in foods taken by respondents have shown disparities and all the iodine values across zones of the state are sufficient. Fish has the highest iodine (56.0 ± 7.01 - 100.1 ± 0.01ppm), then egg (50.1 ± 0.01- 60.0 ± 0.01ppm), then vegetable (39.5 ± 0.01 - 47.3 ± 6.1ppm), followed by chicken (32.7 ± 5.01-45.0 ± 0.001ppm), and lastly, milk (17.0 ± 4.01- 32.6 ± 5.01 ppm). Most of the salts contain adequate iodine. The pattern of the use of salt shows that, about 70% of respondents in Central Sokoto Zone (CSZ), 67.8% in Eastern Sokoto Zone (ESZ) and 69.6 % Western Sokoto Zone (WSZ) sometimes add salt to their meals. The consumption of iodine rich foods reveals, vegetables were the most consumed iodine containing food materials (compared to those that avoids vegetables in the zones of the state), the eggs, followed by milk, and lastly fish. Mostly, there are enough iodine in salts, enough consumption of iodine rich foods, and poor iodine nutrition education among the respondents. More iodine awareness is needed in the state.